Faktor-Faktor yang Mempengaruhi Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Fe: Literature Review - Desi Yunita -Anggraini; Rr. Catur Leny Wulandari; Atika Zahria Arisanti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2022)
Anemia in pregnant women is a condition where there is a lack of red blood cells or hemoglobin. A condition where in the first and third trimesters there is an increase in plasma volume in a greater proportion than the increase in erythrocytes, resulting in a decrease in hemoglobin concentration (Hb) which causes hemoglobin levels to fall below 11.0 g/dl or in the second trimester < 10.5 g/dl. dl due to hemodilution. The purpose of this literature review study was to determine the factors that influence the compliance of pregnant women in consuming Fe tablets. This research method used a literature review method and uses databases such as Pubmed, Google Scholar and Health Profiles with a vulnerable publication period of the last 10 (ten) years. The results from several journals show that there were several factors that influence the compliance of pregnant women in consuming Fe tablets, namely knowledge, attitudes, family support, support from health workers, frequency of ANC visits, and age. Some of these factors show a significant relationship to the effect of pregnant women's compliance in consuming Fe tablets. Conclusion: the factors that influence the compliance of pregnant women in consuming Fe tablets are knowledge, attitudes, family support, support from health workers, frequency of ANC visits, and age.